Influencing Marketing Performance: The Role of Digital Marketing Orientation and Entrepreneurship Orientation through Brand Resonance Capability - Munir, Abdul Razak; Aswan, Andi; Pasyrib, Andi Syahida Ulhaq (International Review of Management and Marketing, 2025)
In an increasingly digital marketplace, businesses face challenges in optimizing their marketing performance while fostering strong brand connections through innovative strategies. This study investigates the influence of Digital Marketing Orientation and Entrepreneurship Orientation on Marketing Performance, mediated by Brand Resonance Capability among small and medium-sized enterprises in Makassar. Utilizing a quantitative approach, data were collected from 230 owners and managers and analyzed using Structural Equation Modeling (SEM). The results reveal that Digital Marketing Orientation and Entrepreneurship Orientation significantly enhance Marketing Performance, with Brand Resonance Capability as a crucial mediator in these relationships. Moreover, the positive impact of Digital Marketing Orientation on Brand Resonance Capability indicates that effective digital marketing strategies foster deeper emotional connections with consumers, ultimately improving loyalty and advocacy. These findings imply that businesses should prioritize integrating digital marketing strategies with entrepreneurial practices to strengthen brand resonance and achieve superior marketing outcomes. By doing so, organizations can navigate the complexities of the digital landscape and enhance their competitive edge.